Advanced DPWM Method for Switching Loss Reduction in Isolated DC Type Dual Inverter with Open-End Winding IPMSM - Lee, Hyung Woo; Jang, Sung Jin; Lee, Kyo Beum (IEEE Access, 2023)
This paper proposes an advanced discontinuous pulse-width modulation (DPWM) scheme for a dual inverter to reduce switching loss. A dual inverter is used to drive an open-end winding interior permanent magnet synchronous motor (OEW-IPMSM). It is composed of double two-level inverters with large switching loss owing to the use of 12 switching devices. When a current phase changes, the switching loss cannot be minimized by using a conventional DPWM scheme. As the conventional DPWM scheme uses reference voltage for switching, the switching loss cannot be minimized due to the difference between the phases of the stator current and phases of reference voltages. However, the proposed DPWM scheme with additional calculations of the current phase can minimize switching loss. When the current phase changes, the proposed DPWM is switched to ±30° of the maximum point of the current. Furthermore, the effectiveness of the proposed switching loss reduction ability is verified through simulations and experimental results.
Keywords: Discontinuous pulse width modulation; Dual inverters; Interior permanent magnet synchronous motor; Inverter; Open-end winding interior permanent magnet synchronoi motor; Open-end windings; Permanent magnet motor; Pulsewidth modulations (PWM); Switching loss; discontinuous pulse width modulation (DPWM); Dual-inverter; open-end winding interior permanent magnet synchronous motor (OEW-IPSM)